Estudo de propriedades ópticas de moléculas de chalconas - Santos, Francisco de Assis (2015)
This work reports on the optical properties of chalcones molecules in solution, using methanol as solvent. For the characterization of the linear optical properties, were obtained absorbance spectra. While for the characterization of the nonlinear optical properties, it has been used techniques hyper-Rayleigh scattering and Z-scan. Using hyper-Rayleigh scattering technique, were determined the first hyperpolarizabilities of the molecules studied. With the Z-scan technique, we could obtain the two-photon absorption spectra at several wavelengths in the range of 480 to 790 nm. From the two-photon absorption spectra were possible to determine the coefficients of two-photon absorption and their respective cross section. The results help to understand the effects of substituents added to the basic structure of chalcones in both linear optical properties as nonlinear.